The persecution of poverty: the judicial power as a protagonic subject in the construction of the others - Campos, Alexia (2017)
The thousands and infinite spaces generated by each of the normative bodies that are sanctioned, make the judicial power a maze that excludes the real victims of criminal action but, mainly, that generates, includes and (re) produces new victims. We intend to demonstrate and analyze, in two particular cases, how the judicial apparatus encourages the patterns of power and domination through the people / groups selected when pursuing. On the one hand, we will analyze a criminal process fraught with irregularities where Emanuel Silva, a boy with delayed maturation and semi-illiterate, is sentenced to 12 years in prison by the Argentine justice system. Irregularities throughout the process are aggressive and obvious. On the other hand, we will problematize a criminal process in the province of Formosa, initiated by a police repression in the face of a peaceful blockade of a road by an indigenous community, in response to a decision of the provincial executive t